Grenada Workforce Development : SABER Country Report 2013 - World Bank (Washington, DC, 2015)
Grenada has faced various socioeconomic challenges within the last decade, including the destruction wrought by Hurricane Ivan in 2004 and the global financial crisis. As a result, economic indicators for Grenada illustrate unfavorable. Increases in the poverty and unemployment rates, especially among the youth and young adults. This report presents an assessment of the regulatory, legislative, and institutional landscape governing workforce development (WfD) in Grenada. The results of this analysis are based on a newly designed analytical tool developed by the World Bank under the Systems Approach for Better Education Results (SABER) initiative. The aim of this initiative is to garner data so as to provide systematic documentation and assessment of the policy and institution factors that influence the performance of education and training systems of SABER-participating countries. The SABER-WfD tool encompasses initial, continuing, and targeted vocational education and training that are offered through multiple channels, and focus largely on programs at the secondary and post-secondary levels. The results of the assessment presented in this report are expected to assist in clarifying priorities. They classify the WfD system according to four stages of maturity in policy and institutional development, as follows: (1) Latent, (2) Emerging, (3) Established, and (4) Advanced.